1. The Balkans at the Turn of the Nineteenth to the Twentieth Centuries - Committee, Editorial (Historein, 2013)
Nikos Sigalas, review of The "lost homelands" beyond nostalgia: a sociocultural-political history of Ottoman Greeks, mid-19th–early 20th centuries, by Haris Exertzoglou. Elias G. Skoulidas, review of "Blessed are those who possess the land": Land-conquering plans for the "disappropriation" of consciences in Macedonia, 1880-1909, by Spyros Karavas. Roumen Daskalov, review of The Balkans: modernisation, identities, ideas; in honour of Prof. Nadia Danova (collective volume). Loring M. Danforth, review of Battlefields of Memory: The Macedonian Conflict and Greek Historical Culture, by Erik Sjöberg. Sada Payır, review of Les Grecs d’Instabul au XIXe siècle: Histoire socioculturelle de la communauté de Pera, by Méropi Anastassiadou. Dimitris Stamatopoulos, review of Society and Politics in Southeastern Europe during the 19th Century, by Tassos Anastasiadis and Nathalie Clayer (eds).